Inactivated Viral Vaccine BBV87 Protects Against Chikungunya Virus Challenge in a Non-Human Primate Model - Sarah L. Kempster; Deborah Ferguson; Claire Ham; Joanna Hall; Adrian Jenkins; Elaine Giles; Simon L. Priestnall; Alejandro Suarez-Bonnet; Pierre Roques; Roger Le Grand; Sumathy Kandaswamy; Sushant Sahastrabuddhe; et al. (Viruses)
Chikungunya virus (CHIKV) is an alphavirus transmitted by mosquitos that poses a threat to global public health and for which there is an urgent need for widespread access to globally licensed vaccines. Here, we demonstrate that an inactivated CHIKV vaccine (BBV87) protects against systemic infection with CHIKV in a non-human primate (NHP) challenge model. Groups of five cynomolgus macaques received two doses of 20 µg BBV87 vaccine or saline alone (28 days apart). Twenty-eight days after the second immunisation, all animals were challenged with CHIKV. All controls were productively infected with detectable viremia and pathological responses following challenge, including altered thermoregulation, haematological and cytokine changes. Critically, the histopathological analysis of finger joints identified areas of inflammation in the synovium. By contrast vaccinated macaques had no detectable viremia and none of the pathological changes were reported in control animals. This study demonstrates that a 20 µg dose of BBV87 vaccine confers robust protection in vivo, both on the acquisition of infection and pathology.